Porous Materials Applied in Nonaqueous Li–O2 Batteries: Status and Perspectives. Issue 44 (26th July 2020) - Wang, Huanfeng; Wang, Xiaoxue; Li, Malin; Zheng, Lijun; Guan, Dehui; Huang, Xiaolei; Xu, Jijing; Yu, Jihong
Abstract: Porous materials possessing high surface area, large pore volume, tunable pore structure, superior tailorability, and dimensional effect have been widely applied as components of lithium–oxygen (Li–O2 ) batteries. Herein, the theoretical foundation of the porous materials applied in Li–O2 batteries is provided, based on the present understanding of the battery mechanism and the challenges and advantageous qualities of porous materials. Furthermore, recent progress in porous materials applied as the cathode, anode, separator, and electrolyte in Li–O2 batteries is summarized, together with corresponding approaches to address the critical issues that remain at present. Particular emphasis is placed on the importance of the correlation between the function‐orientated design of porous materials and key challenges of Li–O2 batteries in accelerating oxygen reduction reaction (ORR)/oxygen evolution reaction (OER) kinetics, improving the electrode stability, controlling lithium deposition, suppressing the shuttle effect of the dissolved redox mediators, and alleviating electrolyte decomposition. Finally, the rational design and innovative directions of porous materials are provided for their development and application in Li–O2 battery systems. Abstract : The application of nonaqueous Li–O2 batteries is limited by challenges from the cathode, anode, separator, and electrolyte. The perspectives of porous materials for Li–O2 batteries are outlined, the advances of porous materials for targeting critical battery challenges are highlighted, and rational design and future directions of porous‐materials‐based Li–O2 battery systems are suggested.